2017
DOI: 10.1002/gps.4782
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported personality traits are prospectively associated with proxy‐reported behavioral and psychological symptoms of dementia at the end of life

Abstract: The present research indicates that self-reported personality, particularly Neuroticism, is associated prospectively with risk for a wide range of behavioral symptoms for individuals who had cognitive impairment at the end of life. The use of self-reported personality traits can help aid in identifying who is most at risk for behavioral symptoms. Such information may be useful for nonpharmacological interventions tailored to the individual's personality to reduce the prevalence and burden of these BPSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 42 publications
(76 reference statements)
2
21
0
Order By: Relevance
“…Mood symptoms and SCD have been shown to interact to predict dementia independent of their main effects [48], and similar results have been found examining persistent neuropsychiatric symptoms and MCI [15]. The approach to psychiatric symptomatology in SCD has generally utilized traditional constructs of personality (e.g., neuroticism) and psychiatric conditions [49][50][51]. However, a change in personality to greater neuroticism (which is a neurodevelopmental construct) can also be framed as the emergence of MBI affective dysregulation, if considered in a neurodegenerative frame of reference [49].…”
Section: Intersection Of Mbi and Scdmentioning
confidence: 75%
“…Mood symptoms and SCD have been shown to interact to predict dementia independent of their main effects [48], and similar results have been found examining persistent neuropsychiatric symptoms and MCI [15]. The approach to psychiatric symptomatology in SCD has generally utilized traditional constructs of personality (e.g., neuroticism) and psychiatric conditions [49][50][51]. However, a change in personality to greater neuroticism (which is a neurodevelopmental construct) can also be framed as the emergence of MBI affective dysregulation, if considered in a neurodegenerative frame of reference [49].…”
Section: Intersection Of Mbi and Scdmentioning
confidence: 75%
“…The approach to psychiatric symptomatology in SCD has generally utilized traditional constructs of personality (e.g. neuroticism) and psychiatric conditions [41][42][43] . However, a change in personality to greater neuroticism ( which is a neurodevelopmental construct) can also be framed as the emergence of MBI affective dysregulation, if considered in a neurodegenerative frame of reference 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Sutin et al, who analyzed people with evidence of cognitive impairment at the end of life, established that the respondents with higher neuroticism were at a significantly greater risk of impaired functioning in many areas, and more often suffered from depression. This association was true, even after exclusion of such interfering factors as age, sex, race, and education [ 65 ]. What is more, the study of Taiwanese climacteric women revealed that neuroticism is an important contributor to the persistence of depression [ 66 ].…”
Section: Discussionmentioning
confidence: 99%